Improving the growth, Chlorophyll contents and productive tillers of wheat by exogenous application of fulvic acid under natural and heat stress conditions - Asif, Muhammad; Ahmed, Siraj; Saqib, Muhammad; Saleem, Muhammad Farrukh; Khan, Haroon Zaman; Sarwar, Muhammad; Shahid, Muhammad Shahid (Journal of Agriculture and Biology, 2023)
Terminal thermal stress, occurring under varying climatic conditions, significantly reduces wheat yield by affecting fertilization and grain filling processes. Wheat crop damage from terminal heat stress may be lessened by the use of biostimulants. The purpose of this study is to apply fulvic acid topically to wheat in order to reduce the effects of heat stress. Wheat crops were subjected to high temperature stress during booting and initial stages of grain in in-vivo, with heat stress applied in staggered intervals in the main plot. Different concentrations of fulvic acid (water spray, 1.25 mg L-1, 2.50 mg L-1, and 3.75 mg L-1) were applied under natural and heat stress conditions during the booting and initial stages of grain of wheat. Heat stress during booting and grain filling phases notably decreased chlorophyll content, growth related parameters and productive tillers. The impact was more significant during the booting stage compared to the filling stage of grain. Application of fulvic acid at concentrations of 3.75 mg L-1 and 2.50 mg L-1 during heat stress at booting and grain filling stages substantially increased chlorophyll content and growth related parameters compared to water spray and 1.25 mg L-1 fulvic acid. These findings imply that fulvic acid applied directly to wheat under heat stress causes thermotolerance, which has a beneficial impact on biochemical and physiological processes.
Keywords: Biostimulant; Growth; Thermotolerance; Triticum aestivum; Yield